DNA variants and population structure of Magelang ducks across generation - Febriana, A.; Kurnianto, E.; Sutopo, S.; Lestari, D. A.; Setiaji, A.; Sugiharto, S. (Diponegoro University, 2024)
Magelang ducks (MD) are Indonesian local ducks and are known as dual-purpose type ducks which have high egg production, duck day production (DDP), and body weight size. Nowadays, the MD is selected to establish the pure line to advance the egg production trait in the Breeding and Rearing Center of Non-Ruminant Animals Banyubiru, Central Java. The mitochondrial DNA (mtDNA) Dloop region, is highly polymorphic and could be used to analyze the population genetics. The present research aims to examine the impacts of continuous selection on population structure and genetic mutations on MD across two generations using the mtDNA D-loop region. Thirty-six blood samples from the second (G2) and third (G3) generations were examined using the sequencing method. The MEGA X and DnaSP software were applied to calculate the genetic diversity, genetic distance, and to generate a phylogenetic tree. The number of haplotypes (H), haplotype diversity (Hd), and Tajima's D are 26, 0.9746, and -1.46, respectively. The Fst value of MD is 0.156. The genetic distance among populations ranges from 0.0000 – 2.097. The UPGMA analysis constructs one clade in a phylogenetic tree between MD, Indonesian local Ducks, Indian Ducks, Vietnamese Ducks, and Chinese Ducks. The study found that the genetic variation and population structure did not significantly change between the second and third generations.